1999
DOI: 10.1046/j.1432-1327.1999.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Pen c 1, a novel enzymic allergen protein from Penicillium citrinum

Abstract: A 33-kDa alkaline serine protease secreted by Penicillium citrinum strain 52-5 is shown to be an allergenic agent in this fungus. The protein, designated Pen c 1, was purified by sequential DEAE-Sepharose and carboxymethyl (CM)-Sepharose chromatographies. Pen c 1 has a molecular mass of 33 kDa and a pI of 7.1. The caseinolytic enzyme activity of this protein was studied. The protein binds to serum IgE from patients allergic to Penicillium citrinum. The cDNA encoding Pen c 1 is 1420 bp in length and contains an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 50 publications
0
52
0
Order By: Relevance
“…We have previously cloned and purified an immunodominant allergen, Pen c 13, from Penicillium citrinum and, using a traditional caseinolytic analysis, characterized it as a serine protease and shown that it contains the conserved catalytic triad motif of serine proteases (27). In the present study, we showed that Pen c 13 induces proinflammatory cytokine release by human airway epithelial cells (HAECs) and activates PARs through the Ca 2ϩ -signaling pathway.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…We have previously cloned and purified an immunodominant allergen, Pen c 13, from Penicillium citrinum and, using a traditional caseinolytic analysis, characterized it as a serine protease and shown that it contains the conserved catalytic triad motif of serine proteases (27). In the present study, we showed that Pen c 13 induces proinflammatory cytokine release by human airway epithelial cells (HAECs) and activates PARs through the Ca 2ϩ -signaling pathway.…”
mentioning
confidence: 63%
“…Pen c 13 was purified to homogeneity from P. citrinum culture medium as described previously (27). Briefly, Pen c 13 was isolated by a combination of anion-exchange (HiTrap DEAE-Sepharose Fast Flow; 0.7 ϫ 2.5 cm) and cation-exchange (HiTrap CM-Sepharose Fast Flow; 0.7 ϫ 2.5 cm) chromatography.…”
Section: Purification Of Pen C 13 From P Citrinummentioning
confidence: 99%
See 1 more Smart Citation
“…Cultures of transformed cells were grown to an A 600 of 0.6, and then expression was induced by addition of 1 mM isopropyl ␤-D-thiogalactoside for 3 h. The recombinant His 6 -ureaseA fusion protein was purified using a Ni 2ϩ chelate affinity column (19). The purified protein showed a single band on SDS-PAGE and was identified by mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…Subtilisin Carlsberg (alcalase) produced by Bacillus licheniformis is frequently used in detergent formulations, and allergic respiratory reactions to alcalase have been reported among exposed factory workers (12,88). More recently, a novel subtilisin homologue with IgE antibody binding properties derived from the fungus Penicillium citrinum was identified (110). This allergen, Pen c 1, has a high degree of amino acid sequence identity to Tri r 2 (J. Woodfolk, unpublished data).…”
Section: Trichophyton Allergens: a Role For Enzymatic Function?mentioning
confidence: 99%